PuTMO3 systems crystal structures prediction and stability analysis based on first principles - Zexin Jiang; Jintao Wang; Yilin Fang; Tao Wang; Rui Zhou; Wenli Yu; Rusong Li; Ning Gao (Scientific Reports)
Abstract Based on particle swarm optimization algorithm and first-principle calculations, the most stable structures of 10 different PuTMO3 systems are predicted according to their thermodynamical, mechanical and dynamical properties. The results indicate firstly all selected 50 structures are thermodynamically stable based on formation enthalpy results. 29 of the 50 structures are then predicted to be mechanically stable according to mechanical stability criterion for different structures. And then 10 of 29 structures are selected to be dynamically stable based on calculations of phonon frequency, that is, PuTiO3(Cc, Pca2_1), PuZnO3(Pca2_1, P2_1/m), PuGaO3(C2/m), PuMnO3(Pna2_1), PuNiO3(P4_1), PuFeO3(C222_1), PuVO3(P2_13), and PuCrO3(P2_13). Finally, the electronic properties of these 10 structures were calculated. All these results provide useful information to manufacture Pu-based MOX fuels by controlling impurities through formation of PuTMO3 compounds and the recycling of materials in recovery process.